Impact of Brand Image, Product Quality, and Influencers on Compass Shoe Purchases - Andoko, Aldi; Rukmini, Meme (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
In the contemporary period of globalization and information technology development, competition in the fashion industry, especially shoes, is becoming increasingly fierce. The local shoe brand that is currently popular in Indonesia is Compass. Compass's popularity is increasing, supported by well-known influencers in Indonesia. Apart from influencers, product quality and brand image are also important factors in influencing decisions about purchases. The purpose of this study is to ascertain how much influencers, product quality, and brand perception have on purchasing decisions to purchase Compass shoes. Data collection was carried out by distributing questionnaires to 100 students in Kediri City. The study's findings indicate that Influencer has a significant impact on consumer behavior, but product quality has no significant impact on consumer behavior. Citra Merek, on the other hand, has a significant impact on consumer behavior. However, if Influencer, Product Quality, and Citra Merek are combined, the results show that they have a significant positive impact on the purchase of Sepatu Compass among students in Kediri. Keywords: Influencer, Brand Image, Product Quality